Women with a history of gestational diabetes mellitus present an accumulation of cardiovascular risk factors at age 46—A birth cohort study - Evi Bakiris; Kaisu Luiro; Jari Jokelainen; Laure Morin‐Papunen; Sirkka Keinänen‐Kiukaanniemi; Kari Kaikkonen; Terhi Piltonen; Juha S. Tapanainen; Juha Auvinen (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The incidence of gestational diabetes mellitus (GDM) is globally increasing, and it has been associated with later type 2 diabetes, metabolic syndrome (MetS), and cardiovascular disease (CVD). However, long‐term population‐based studies investigating common CVD risk factors years after pregnancy are lacking. To evaluate the future mortality and morbidity in cardiovascular and metabolic diseases, we conducted a thorough investigation of midlife risk factors in women with and without previous GDM. Material and Methods A prospective population‐based cohort study was conducted of 3173 parous women from the Northern Finland Birth Cohort, 1966. Study participants were obtained from the national register or patient records. Those with a GDM diagnosis formed the GDM cohort (n = 271), and those without a previous GDM diagnosis formed the control cohort (n = 2902). Clinical examinations were performed on participants at the age of 46 and included anthropometric measurements, oral glucose tolerance test (OGTT), biochemical measurements, and cardiovascular assessment. Results At the age of 46, women in the GDM cohort had a higher body mass index (BMI, 29.0 kg/m2 vs 26.3 kg/m2, p < 0.001) and greater waist circumference (94.1 cm vs 86.5 cm, p < 0.001) than the control cohort. In the GDM cohort, a higher incidence of impaired glucose tolerance (12.6% vs 7.3%, p = 0.002), more previously diagnosed and OGTT‐detected type 2 diabetes (23.3% vs 3.9%, p < 0.001), lower high‐density lipoprotein (1.53 mmol/L vs 1.67 mmol/L, p = 0.011), higher triglycerides (1.26 mmol/L vs 1.05 mmol/L, p = 0.002) and a higher fatty liver index (6.82 vs 2.47, p < 0.001), were observed even after adjusting for BMI, polycystic ovary syndrome, parity, level of education, physical activity, smoking, and alcohol consumption. The women in the GDM cohort also had more MetS (42.6% vs 21.9%, p < 0.001) and higher risk scores for CVD and fatal events (Framingham 4.95 vs 3.60, p < 0.001; FINRISK 1.71 vs 1.08, p < 0.001). Conclusions Women with a previous diagnosis of GDM exhibit more risk factors for CVD in midlife and are at a higher risk for cardiovascular events later in life.